The Structure of the Australian Party System and its Strategic Consequences - Charnock, David; Ellis, Peter (Routledge, 2003)
In this paper we explore the positioning of Australian political parties at the 2001 federal election using data from the Australian Election Study and discuss some of the strategic implications. We focus on some of the attitudes of Senate voters for the various parties, concentrating on how Inglehart's postmaterialism measures and a measure of postmodern attitudes can be used to supplement more traditional left-right descriptions of the party system. We find that descriptions based on a single left-right dimension are inadequate but that attitudes on this dimension and on a postmaterialism or postmodernism dimension are correlated, thus creating constraints for parties. We use comparisons with the 1998 election to assess the stability of the structure and the significance of the electoral context, and generally find that the structure was stable between the two elections.